Enhancing the Capacity of Forest Farmer Groups (KTH) Through the Payment for Environmental Services (PES) Model Scheme - Wahyullah, Wahyullah; Arsyad, Usman; Makkasau, Ahmad Rifqi; Wahyuni, Wahyuni; Amaliah, Rizki; Molo, Hasanuddin; Misto, Misto; Rafrin, Syaifullah; Haerani, Nurul (Journal of Mestika Nusantara Satu Community Services, 2024)
Payment for Environmental Services (PES) is an environmental service compensation activity conducted by Forest Programme IV (FP-IV), designed to be implemented in the Mamasa Sub-Watershed of the Saddang Watershed. The implementation of this PES plan will be collaborated with parties such as the Bakaru Watershed Forum, Hydroelectric power plant (PLTA), and Forest Farmer Groups (KTH) in selected villages over a 5-year contract. However, the challenge is that the target community lacks trust in PES activities and most refuse to join, making the formation of KTH Mappideceng problematic. The purpose of community service is to enhance the capacity of KTH Mappideceng based on the requirements and criteria established by the PES model scheme. The methods used include primary socialization (door-to-door) such as surveys, lectures, and discussions. The results of the community service activities in KTH Mappideceng, Betteng village, showed an increase in the number of members from 12 to 21, with 15 being new members and 6 being existing ones. After the socialization carried out by the team, enthusiasm and motivation to join increased; however, the intervention location and funding limitations were predetermined by the PES model mechanism (FP-IV).